Physicochemical and biological characterization of functionalized calcium carbonate - Sirkiä Saara V.; Qudsia Syeda; Siekkinen Minna; Hoepfl Wolfgang; Budde Tanja; Smått Jan-Henrik; Peltonen Jouko; Hupa Leena; Heino Terhi J.; Vallittu Pekka K. (Elsevier B.V., 2025)
Biocompatible and osteoconductive calcium carbonate (CC) and hydroxyapatite (HAP) have been studied as bone filling materials. In contrast to HAP, CC is highly resorbable, and to achieve optimal resorption rates, a functionalized calcium carbonate (FCC) consisting of CC particles with a HAP layer has been further developed. The aim of this study was to characterize the physicochemical and biological properties of FCC.
Physicochemical properties were studied with ATR-FTIR, XRD and SEM. pH change and ion release were studied in a static system in cell culture medium or water, and in a continuous dynamic system in Tris-buffer. Viability and morphology of pre-osteoblastic cells in vitro was studied with a WST method, as well as with SEM and TEM imaging.
There was a minor increase in pH in Tris-buffer and water dissolution systems at the beginning of FCC dissolution. In contrast, pH of the cell culture medium remained approximately unchanged during the dissolution. In Tris-buffer and water dissolution systems, increased levels of calcium release from FCC were detected, whereas in the cell culture medium FCC was shown to adsorb calcium from the medium, thus causing a decrease in the dissolved calcium concentration. This was associated with decreased viability of cells. Interestingly SEM and TEM imaging revealed internalization of FCC particles by the cells.
This study showed that FCC, similar to natural bone mineral, carbonated apatite has a capability to adsorb calcium from surrounding liquid. This needs to be carefully considered when cell culture assays are performed with these types of materials.